Analysis of Preventive Maintenance System Using the MTBF and MTTR Method - Adjie Ayyub Rajendra Akash; Hafid Syaifullah (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The reliability of production machinery plays a crucial role in ensuring the continuity of manufacturing processes, as machine disturbances or failures can lead to downtime, reduced productivity, and increased operational costs for the company. This applied study was conducted at PT XYZ, a ceramic manufacturing company established in 1971 and recognized as one of the largest ceramic producers in Indonesia, with a focus on the Engineering Department, particularly the machine maintenance system on Line 3, which includes the press machine, glazing line, and kiln. The evaluation was carried out on the implementation of Preventive Maintenance using the Mean Time Between Failures (MTBF) and Mean Time To Repair (MTTR) approaches, based on machine downtime data for the September 2025 period. The objective was to identify the level of machine reliability, calculate the average time between failures, and determine the average repair duration in order to support the smooth operation of the production process.